Race day! - Tuchman, Gail. (Washington, D.C. : National Geographic, 2010)
Photographs and text take readers inside the action at a race car competition.
"National Geographic Kids"--Cover.
0.9
K-3
K-3
Keywords: Automobile racing -- Juvenile literature; Automobile racing; Automobile racing; Readers (Elementary)